A Probabilistic Neural Network Measurement Method for Multispectral High Dynamic Temperature. (1st March 2023) - Zeng, Chaobin; Liu, Bin; Zhang, Xuan; Han, Yan
Abstract: Among various temperature measurement technologies, Multispectral thermometry is a better method to measure temperature under complex conditions. To solve the problems in the multi-spectral temperature measurement technology, which included the detector's non-linear sensitivity characteristics, consistency calibration, data processing, etc., this paper, based on the previous research and development of the multi-spectral dynamic temperature measurement system, realized data acquisition of the dynamic temperature in 20us sample rates within 1550 2000 Celsius, and then the dynamic measurement data is processed by the probabilistic neural network (PNN). Finally, temperature measurement system realized the accuracy of the measurement error less than 1.1%. The results show that the PNN neural network can fit the temperature distribution curve better and faster, and can be better applied to the miniaturization of the temperature measurement system.